Magnesium stearate-coated superhydrophobic sponge for oil/water separation: Synthesis, properties, application - Parsaie, Aliasghar; Mohammadi-Khanaposhtani, Mohammad; Riazi, Masoud; Tamsilian, Yousef (Separation and purification technology, 2020)
•Synthesis of a robust superhydrophobic/superoleophilic polyurethane sponge comprising magnesium stearate nanoparticles coating and phenol-formaldehyde resin for the removal of organic materials and oil from the oil/water system.•Well coating sponges with the nanoparticles-resin mixture to alter the surface wettability by the cost-effective immersion method.•High oil absorption capacity (29–38 times their own weight depending on different the pollutant density and viscosity) and high absorption rate lower than 1 s.•High water contact angle (greater than 175°) and siliding angle less than 3°.•Great performance (only 2–7° in decreasing water contact angle) for the superhydrophobic sponge in harsh conditions such acidic/basic environment, and abrasion. Separation of an oil/water mixture has become a very attractive subject due to frequent oil spill incidents and industrial oily wastewater treatment. In this study, a robust superhydrophobic/superoleophilic polyurethane sponge comprising magnesium stearate coating and phenol-formaldehyde resin was developed by the cost-effective immersion method for the removal of organic materials and oils from the oil/water system. The characterizations of the modified polyurethane by SEM, FESEM, FTIR, Raman and EDX confirmed that it was well coated with phenol-formaldehyde and magnesium stearate. The water contact angle measurement results showed a contact angle exceeding 175° and sliding angle less than 3°, which are, compared to other reports up to now, a great unprecedented achievement. Also, no considerable change after abrasing and immersing in the acidic and basic solution was observed. Due to outstanding water contact angle, the organic absorption time is less than 1 s, covering a wide absorption capacity range of 19–38 g/g depending on the viscosity and density of oils and organic solvents. Finally, the modified polyurethane sponge provided an excellent performance capability of the continuous oil/water separation, required for an industrial application.